Exploring the Relational Dynamic among Customer Relationship, Customer Experience, and Loyalty in Guarantee Services - Anggraini, Ni Putu Nita; Widyaningtyas, Putu Bunga; Wijana, I Made Dauh (Universitas Pendidikan Ganesha, 2025)
Inconsistent findings on how customer relationship and experience influence loyalty highlight the need to explore the mediating role of satisfaction and self-congruence, particularly in the MSME guarantee service context. This study investigates the relational dynamics between customer relationship, customer experience, satisfaction, and loyalty within the MSME-guarantee service context of PT Jamkrida Bali Mandara. Drawing on Self-Congruence Theory (SCT), the research examines customer satisfaction as a mediating mechanism linking relational and experiential factors to loyalty. Using a quantitative approach with 183 institutional respondents and data analyzed through Structural Equation Modeling–PLS, the findings reveal that both customer relationship and customer experience significantly influence loyalty, partially mediated by satisfaction. These results validate SCT in an institutional service setting, suggesting that loyalty arises not only from functional interactions but also from psychological congruence between customer self-concept and organizational values. The study contributes theoretically by extending SCT to the guarantee service sector and provides managerial implications emphasizing the importance of enhancing relationship quality, customer experience, and satisfaction to strengthen long-term loyalty.